Biomarker-specific differences between transpulmonary and peripheral arterial–venous blood sampling in patients with pulmonary hypertension. (17th February 2020) - Meoli, David F.; Clark, Daniel E.; Davogustto, Giovanni; Su, Yan Ru; Brittain, Evan L.; Hemnes, Anna R.; Monahan, Ken
Abstract: Purpose : Transpulmonary biomarkers may provide insight into pulmonary hypertension (PH) pathophysiology, but require cardiac catheterization. We investigated whether the peripheral arterial–venous ratio (PR) could substitute for the transpulmonary ratio (TPR). Materials and methods: Blood from the pulmonary artery (PA), pulmonary arterial wedge (PAW), peripheral venous, and peripheral arterial positions was analysed for ET-1, NT-pro-BNP and cAMP levels in subjects with no PH ( n = 18) and PH due to left heart disease (PH-LHD), which included combined pre- and post-capillary PH (Cpc-PH; n = 7) and isolated post-capillary PH (Ipc-PH; n = 9). Bland–Altman comparisons were made between peripheral venous and PA samples and between peripheral arterial and PAW samples. TPR was defined as [PAW]/[PA]. Results: For ET-1, Bland–Altman analysis indicated negative bias (−24%) in peripheral arterial compared to PAW concentration and positive bias (23%) in peripheral venous compared to PA concentration. There was <10% absolute bias for NT-pro-BNP and cAMP. For ET-1, there was no difference in PR between Cpc-PH and Ipc-PH (0.87 ± 0.4 vs. 0.94 ± 0.6, p = 0.8), whereas there was a difference in TPR (2.2 ± 1.1 vs. 1.1 ± 0.2, p < 0.05). Conclusions: In PH-LHD, peripheral samples may be inadequate surrogates for transpulmonary samples, particularly when measuring mediators with prominent pulmonary secretion or clearance, such as ET-1.